Pengaruh Digitalisasi Terhadap Efisiensi dan Efektivitas Proses Akuntansi Pada Koperasi Pesantren - Anshari, Muhammad Irham; Rola Manjaleni (Forum Kerjasama Pendidikan Tinggi, 2024)
This study aims to identify the effect of digitalization on the efficiency and effectiveness of accounting processes. The rapid development of information technology in the current 5.0 era increases business productivity and efficiency. Globalization and digitalization are changing the way people do things. The increasing number and role of cooperatives in Indonesia. However, there are still many cooperatives, especially pesantren cooperatives, that have not utilized digital technology in the accounting process. There are many cooperatives, especially pesantren cooperatives, that still use manual systems in accounting processes, such as financial recording, reporting, and data storage. This manual system is inefficient and prone to errors. This causes difficulties in financial management and decision making. This research uses quantitative methods. Questionnaires were distributed to 30 respondents to collect quantitative data from a sample of digital application users. The results of data analysis show that digitalization has a positive and significant effect on the efficiency and effectiveness of the accounting process. The effect of Digitalization on the Efficiency of the accounting process in Pesantren cooperatives in West Java is 89.4%. Meanwhile, the effect of digitalization on the effectiveness of the accounting process at Pesantren cooperatives in West Java is 88.8%. In addition, digitalization can improve the efficiency and effectiveness of the accounting process. Furthermore, the results of this study indicate that digitalization is a useful tool for pesantren cooperatives to improve the efficiency and effectiveness of the accounting process.